A colonização neoliberal de Jerusalém após Oslo: desenvolvimento, pacificação e resistência em Palestina/Israel - Huberman, Bruno (2020)
Since the 2000s, the Israeli government of East Jerusalem began to implement a series of policies for the development and integration of its Palestinian residents and their spaces of living after social upheavals by both Palestinians and Israelis. These policies underscored by the neoliberal reason for urban revitalization, professional training and the advancement of entrepreneurship represent a contradiction to the history of alienation, dispossession and de-development of East Jerusalem by Israeli colonial power for the city socio-spatial Judaization. However, the exclusion measures were not interrupted during this inclusion phase. This thesis focuses on the contradiction between the rise of neoliberal development policies by Israeli actors in East Jerusalem and the continuity of colonial policies that some might consider "illiberal". In opposition to those who understand this ambivalent entanglement between colonial and neoliberal measures as a paradox, antagonistic or the construction of decolonial neoliberal multiculturalism, this investigation argues that colonialism and neoliberalism are phenomena that express singularities of capitalist universality. Their combination allows the primitive accumulation of capital to occur permanently by explicitly coercive and force-based forms, and also by progressive and humanized means that function as a fraudulent technology for the dispossession and control of subalterns in Jerusalem. Based on the analysis of race and class relations in Jerusalem, we argue that progressive neoliberalism and entrepreneurial urbanism would be depoliticized instruments of pacifying Palestinians and silencing working-class Israelis. Neoliberal colonialism is the synthesis of the contradictions between its hard and soft technologies that allow the reproduction of the colonial government and its racial inequalities as "natural" results of market relations. The neoliberal hegemony over the settler colonial regime social regulation allows the reduction of its vulnerabilities, as in the formation of a neoliberal anti-colonialism in the Palestinian resistance